2011
DOI: 10.1051/0004-6361/201015410
|View full text |Cite
|
Sign up to set email alerts
|

Binary progenitor models of type IIb supernovae

Abstract: Massive stars that lose their hydrogen-rich envelope down to a few tenths of a solar mass explode as extended type IIb supernovae, an intriguing subtype that links the hydrogen-rich type II supernovae with the hydrogen-poor type Ib and Ic. The progenitors may be very massive single stars that lose their envelope due to their stellar wind, but mass stripping due to interaction with a companion star in a binary system is currently considered to be the dominant formation channel. Anticipating the upcoming automat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
149
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(160 citation statements)
references
References 73 publications
8
149
2
1
Order By: Relevance
“…Binary stellar evolution codes can explain the progenitor structures by Roche lobe overflow (e.g. Benvenuto et al 2013), although attempts to reproduce the observed rates have so far not been successful (Claeys et al 2011). The search for a binary companion to SN 2011dh will provide a crucial test for the binary progenitor hypothesis, as it did for SN 1993J (Maund et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Binary stellar evolution codes can explain the progenitor structures by Roche lobe overflow (e.g. Benvenuto et al 2013), although attempts to reproduce the observed rates have so far not been successful (Claeys et al 2011). The search for a binary companion to SN 2011dh will provide a crucial test for the binary progenitor hypothesis, as it did for SN 1993J (Maund et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Simulations of binary evolution show that the final amount of stripping of the exploding star depends mainly on the initial masses of the two stars in the binary system, the spatial configuration of the system, and the metallicity of the stars. Within the parameter space explored by Yoon et al (2010) and others, both SNe IIb and Ib are produced in a bimodal fashion, but not at the observed rates (e.g., Li et al 2011; see also Claeys et al 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Two main mechanisms have been suggested to produce SE SNe: either binary mass transfer (e.g., Iben & Tutukov 1985;Yoon et al 2010;Claeys et al 2011;Dessart et al 2012;Yoon 2015) or strong line-driven winds from massive Wolf-Rayet (WR) stars (e.g., Conti 1976;Smith 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the close-binary evolution scenario offers an attractive solution to both core-collapse SN statistics (see, e.g., Podsiadlowski et al 1992;Eldridge et al 2008;Smith et al 2011) and inferred ejecta properties (Ensman & Woosley 1988;Woosley et al 1995), it is not clear today what fraction arises from the explosion of stars that evolve in isolation. The diversity of massive close binaries can qualitatively explain the observed diversity of SNe IIb (Claeys et al 2011), but for moderate main-sequence masses, the binary channel seems to favour the production of SNe ‹ email: Luc.Dessart@oca.eu Ib (Yoon et al 2010). The distinction between SNe Ib and Ic, which is observational (Wheeler & Levreault 1985;Harkness et al 1987;Filippenko et al 1990;Wheeler et al 1987), is challenged by the presence of broad lines, causing blending/overlap, and the difficulty of exciting He I (Lucy 1991).…”
Section: Introductionmentioning
confidence: 99%